A Systematic Review on the Use of Big Data in Tourism - Jafar Ahangaran; Abbas Sadeghnia (گردشگری و اوقات فراغت)
As technology advances and the use of social networks and the Internet grows, there's a significant increase in the production of data. The concept of "big data" is becoming more prominent in various scientific studies. However, understanding how big data is used in tourism is a challenge addressed in this study. The research investigates the application of big data in tourism studies published from 2016 to 2022, aiming to identify research gaps and potential areas for future development. To provide an overview of published works in tourism, we used the systematic mapping study method. Articles were assessed based on various factors, including research topic, conceptual and theoretical descriptions, data sources, data types and sizes, data collection methods, data analysis techniques, and reporting and visualization methods. The findings indicate a growth in research within hospitality and tourism management using analytical techniques for big data. Despite this, the research in this field is scattered and limited in scope and methodology, revealing several gaps. Additionally, the study suggests that the full potential of big data remains untapped in tourism, offering numerous research opportunities for the industry. A notable challenge highlighted is the .researchers' incomplete knowledge of data-driven analysis and decision-making tools in this field. 1. Introduction The speed of technological changes and their profound effects on various industries, coupled with unpredictable events such as the recent pandemic—having a significant impact on various sectors—requires these industries to cope with uncertainty (Piyush Sharma, 2020). Among them, dynamic, fluctuating, and time-sensitive industries like the tourism sector must respond promptly and more efficiently to emerging challenges and threats in order to survive (Vikrant Kaushal, 2021). Hence, the roles of technology and digitization are vital in helping industries, countries, and organizations overcome rapid challenges (Soluk, 2021). Digitization and the adoption of new technologies have been increasing dramatically in recent years (Ritter, 2020). This includes the use of methods that change the business model to create more effective and efficient processes toward technology—arguably the most crucial change in exploitation. One significant aspect is the analysis of consumer behavior, market dynamics, supply and delivery processes, and customer communication using data obtained from the digitization process (Youssef, 2021). Meanwhile, big data stands out as one of the most well-known paradigms of information analysis, attracting both researchers and experts (José Álvarez García, 2023). Methodologically, big-data-based approaches allow researchers to overcome the problems associated with traditional sampling methods because big data practically enables working with the entire population under investigation. This capability makes it possible to address any question related to the opinions, views, ideas, and behavior of all individuals. Simultaneously, it proves to be a powerful tool for addressing new research questions, developing innovative research designs useful in advancing knowledge, and ultimately providing support for policy and managerial decision-making (Gerard, 2016). The most crucial factor is that the tourism industry grows based on information. Thus, tourism research requires a large amount of strong, up-to-date, timely, and relevant information to support and assist decision-making processes. Big data can provide up-to-date and highly informed inferences about human behavior and activities that boost the tourism industry (Feifei Xu, 2020). Through the traveler, a large number of data sources can inform decisions made at different stages, such as before, during, and after the trip. One popular data source is social media, used by tourists and tourism businesses to communicate, find or provide relevant information or advice, and obtain information about important news and crises (Park, 2019). Therefore, considering the importance of using big data analysis in tourism studies and stating the issue that no monitoring and analysis of the state of research conducted in this field with this theme has been done so far, the upcoming research on the analysis of the use of big data is focused on tourism research by conducting a systematic mapping review.